Chemical constituents of Phoebe grandis (NEES) Merr, Phoebe tavoyana (MEISSN.) HK.F., and Actinodaphne sesquipedalis Hook. F. Var. glabra and their biological activities / Hanita Omar - Hanita, Omar (2015)
Chemical Constituents of Phoebe grandis (Nees) Merr, Phoebe tavoyana (Meissn.) Hk.F., and Actinodaphne sesquipedalis Hook. F. var. glabra And Their Biological Activities Twenty extracts of Phoebe grandis and Phoebe tavoyana; and Actinodaphne sesquipedalis were underwent preliminary screening for their cytotoxicity, antioxidant, antibacterial and antiplasmodial activities. The potential extracts were chosen for detailed phytochemical investigation involving isolation of compounds by chromatographic methods, structural elucidation by means of spectroscopic methods such as UV, IR, MS, 1D and 2D NMR (COSY, HMQC, HMBC, NOESY) and also by comparison with the literature. Further bioassay screenings for some of the identified compounds were also carried out. These techniques have led to the isolation and identification of several isoquinoline type such as aporphine, proaporphine, oxoaporphine, benzylisoquinolines; morphinandienone and sterols. The crude extracts and some of the isolated compounds were screened for cytotoxic, antioxidant and antibacterial activity, using MTT (Microculture Tetrazolium salt), DPPH (1,1-diphenyl-2-picrylhydrazyl), FRAP (ferric reducing ability of plasma) and disc diffusion methods, respectively. The cell lines used in the cytotoxic assay were MCF-7 (human estrogen receptor (ER+) positive breast cancer), Caov-3 (Human Ovarian cancer cell line) and HepG2 (Human Liver cancer). The antibacterial activity was tested against selected pathogenic bacteria Bacillus subtilis (gram-positive), Staphylococcus aureus S1434 (gram-positive), Staphylococcus epidermidis (grampositive), Escherichia coli (gram-negative), Salmonella typhi (gram-negative), Pasteurella multocida (gram-negative), Enterobacter cloacae (gram-negative) and Methicillin resistant Staphylococcus aureus (MRSA) (gram-positive). Phytochemical study on P. grandis leaves has led to the isolation of two new proaporphine alkaloids litsericinone (55) and 8,9,11,12-tetrahydromecambrine (56) along with two known oxoaporphine lysicamine (54) and dicentrinone (58); one known proaporphine hexahydromecambrine A (57). Interestingly, all of compounds were reported for the first time present in the leaves of P. grandis. Phytochemical work of P. grandis bark yielded β-sitosterol (59), stigmasterol (60), boldine (5), Nmethyllaurotetanine (51), reticuline (61) and laurolitsine (6). However, investigation of the leaves of P. tavoyana afforded seven alkaloids of which two were new compounds; tavoyanine A (63) and tavoyanine B (64) along with four known aporphines; laetanine (62), roemerine (20), laurolitsine (6) and boldine (5); and one morphinandienone, sebiferine (22). Phytochemical study has also been performed on A. sesquipedalis leaves and has yielded eight compounds, β-sitosterol (59), dicentrine (52), Nmethyllaurotetanine (51), stigmasterol (60), dicentrinone (58), boldine (5), norisocorydine (65) and laurolitsine (6); and another five compounds have been isolated from the fruits which consists of three alkaloids were dicentrine (52), liriodenine (19) and dicentrinone (58) and two sterols were β-sitosterol (59) and stigmasterol (60). All compounds, except dicentrine (52) have been isolated for the first time from A. sesquipedalis. Lysicamine (54) and litsericinone (55), exhibited cytotoxic activity against MCF7 and HepG2 cell lines. While, 8,9,11,12-tetrahydromecambrine (56) and hexahydromecambrine A (57) exhibited cytotoxic activity against the HepG2 cell line. 8,9,11,12-tetrahydromecambrine (56) and hexahydromecambrine A (57) were not toxic towards the MCF7 cell line. Lysicamine (54) also displayed a strong antibacterial activity against Staphylococcus aureus with inhibition zones of 13.33 ± 0.57 mm. While, roemerine (20), laurolitsine (6), boldine (5) and sebiferine (22) displayed significant inhibition activity against P. falciparum (3D7).